Perceptions of Modulatory Factors in Migraine and Epilepsy: A Multicenter Study - Ur Özçelik, Emel; Lin, Katia; Mameniškienè, Ruta; Sauter Dalbem, Juiane; Siqueira, Heloise Helena; Samaitienė, Rūta; Vega Zeissig, Luz Eleonora; Fonseca, Armando Ferreira; Mazini Alves, Juliana; dos Santos Lunardi, Mariana; de Queiroz, Luiz Paulo; Zubavičiūtė, Erika; et al. (Frontiers in Neurology, 2021)
Background: Migraine and epilepsy are both common episodic disorders, typically precipitated or inhibited by some modulatory factors (MFs). Objective: To assess the self-perception of MFs in patients with migraine (PWM) compared to patients with epilepsy (PWE) with a standardized protocol in different countries. Methods: Transcultural multicenter comparative cross-sectional study. All consecutive patients who fulfilled the ICHD-3 criteria for migraine and ILAE's criteria for epilepsy, with at least one year of follow-up were interviewed with a semi-structured questionnaire on clinical and epidemiological data and were asked to identify all experienced MFs from a provided list. Results: A total of 608 individuals were surveyed at five university referral centers in Brazil, Guatemala, Lithuania and Turkey. Two hundred and nineteen (91.6%) PWM and 305 (82.7%) PWE identified attack precipitating factors (PFs; p <0.001). The most frequent three PFs reported by epilepsy patients were: "lack of sleep" (56.6%), "emotional stress" (55.3%), "negative feelings" (53.9%), while among migraine patients "emotional stress" (81.6%), "lack of sleep" (77.8%), "negative feelings" (75.7%) were cited. Inhibitory factors (IFs) for the episodes were reported by 68 (28.5%) PWM and 116 (31.4%) PWE. "Darkness" was the most common one, described by 35.6% of PWM whereas "positive feelings" reported by 10.6% of PWE. Most MFs are concordant across the countries but some transcultural differences were noted. Conclusion: The MFs of migraine and epilepsy attacks and their varying frequencies according to different countries were investigated with the same standardized questionnaire, for the first time. MFs were recognized very often in both migraine and epilepsy cohorts, but in distinct disease-specific prevalence, being more frequent in migraine. Recognition of self-perceived MFs may be helpful for the management of both illnesses.